2019
DOI: 10.3390/molecules24193452
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Aurantio-Obtusin-Induced Hepatotoxicity in Rats for Discovery of Potential Biomarkers

Abstract: Aurantio-obtusin is an anthraquinone derived from Cassia obtusifolia (cassiae semen). It is also used as a tool and a detection index for the identification of cassiae semen, as stipulated by the Chinese Pharmacopoeia. Anthraquinones, the main components in cassiae semen, have been reported to show hepatotoxicity. This study investigates the hepatotoxicity of aurantio-obtusin in male Sprague–Dawley rats. We randomly divided the animals into a blank control group and treated three test groups with different dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In our previous study, we reported that aurantio-obtusin could cause liver injury in rats from the perspective of serum metabolomics combined with biochemical, hematological, and pathological indicators. We also found metabolic alterations in liver injury, including metabolism of amino acids (e.g., vanylglycol, phosphopantothenoylcysteine, and dehydroalanine) and lipids (e.g., cholic acid, taurodeoxycholic acid, and phosphatidylcholines) in a serum metabolomics study ( Xu et al., 2019 ). At present, there is no metabolomics applied to the study of urinary metabolism after aurantio-obtusin administration.…”
Section: Introductionmentioning
confidence: 76%
“…In our previous study, we reported that aurantio-obtusin could cause liver injury in rats from the perspective of serum metabolomics combined with biochemical, hematological, and pathological indicators. We also found metabolic alterations in liver injury, including metabolism of amino acids (e.g., vanylglycol, phosphopantothenoylcysteine, and dehydroalanine) and lipids (e.g., cholic acid, taurodeoxycholic acid, and phosphatidylcholines) in a serum metabolomics study ( Xu et al., 2019 ). At present, there is no metabolomics applied to the study of urinary metabolism after aurantio-obtusin administration.…”
Section: Introductionmentioning
confidence: 76%
“…All animals were accepted 1 week of adaptive feeding before the experiment and sacrificed after 8-weeks treatment. For in vivo experiments, the doses of AO (5,10 and 15 mg/kg) were selected based on recent publications ( Xu et al, 2019 ; Guo et al, 2021 ). In chronic HFSW experiment (n = 6), mice were divided into five groups: 1) control group (chow diet); 2) NAFLD model group [HFSW, Western diet-42% Kcal from fat and 0.2% cholesterol (TD.88137, Harlan Laboratories, Inc., Indianapolis, IN, United States) plus with a high sugar solution ( d -fructose: 23.1 g/L and d -glucose: 18.9 g/L) in drinking water ( Li et al, 2021 )]; (3–5) HFSW diet with AO administration group.…”
Section: Methodsmentioning
confidence: 99%
“… “N”=negative, “P”=positive, “-”=not found. * in vivo results cited from the literature ( Program, 2001 , Wang et al, 2009 , Xu et al, 2019 , Yang et al, 2019b ). …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3 , Nos. 2 , 3 , 5 , 8 , 10, and 11 were reported to be hepatotoxic in vivo ( Program, 2001 , Wang et al, 2009 , Xu et al, 2019 , Yang et al, 2019b ), while only No. 10 was known to be nephrotoxic ( Wang et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%